Review of the Conceptual Understandings of the Economic Risks - Marikina, Maria (Research Papers, 2021)
Conceptual understandings of risk have a long history and the object of this publication is related to the economic interest and analysis in economic risks. The aim of the research is to study the main conceptual understandings in the formation of the theory of economic risk, with the next set of tasks: 1. Chronological review of the main ideas of economic risk. 2. Synthesis of modern understandings of this economic category. An original author's methodology is applied in order to light up on the significant conceptions of the risk.
Keywords: Economic risk; Economic theories; Risk